Labelling alcoholic beverages as an instrument of consumer health protection – legal aspects - Wojciechowski, Paweł (Przegląd Prawa Rolnego, 2025)
Alcoholic beverages are a special type of food as their consumption carries significant health and social risks. Given these risks, it is necessary to introduce instruments aimed at reducing this consumption. One such instrument is the regulations on the content and manner in which information on the labels of alcoholic beverages is conveyed to potential customers. The author presents EU and Polish regulations on the labelling of alcoholic beverages and provides a critical analysis of these regulations. He argues in the conclusion that the current rules governing the labelling of alcoholic beverages are insufficient to ensure that consumers can make informed choices about alcoholic beverages and in consequence, and fail to achieve successfully the key objective of food law, i.e. the protection of consumer health. De lege ferenda the author proposes changes to regulations at both the EU and national level to ensure that the labelling of alcoholic beverages contributes to raising public awareness of the negative health and social effects of alcohol consumption and enables consumers to make informed choices between alcoholic and non-alcoholic beverages. In the author's opinion, the content and aesthetics of alcoholic beverage labels should discourage alcohol consumption rather than promote alcoholic beverages and increase alcohol sales and, consequently, consumption, as is the case under the current legal framework.